2022
DOI: 10.2528/pierl22013001
|View full text |Cite
|
Sign up to set email alerts
|

U-Slotted Elliptical Shape Patch Antenna for Uwb on-Body Communications

Abstract: An elliptical shape patch (ESP) antenna with inverted U-shaped slots is proposed and presented in this paper for on-body communications. A coplanar waveguide (CPW) feed is used as ground to produce impedance matching, and inverted U-shaped slots are used to produce the ultrawideband (UWB). The proposed ESP antenna model covers UWB characteristics in free space, and it is observed at 3 to 10.7 GHz. When it is implanted on a flat tissue model of human body, the bandwidth is 2.2 to 10.8 GHz. The SAR values of 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In Refs. [28][29][30][31][32][33][34][35][36][37], we can find several useful antennas having the same behaviour when they are deposited directly on the skin. For example, Ref.…”
Section: F I G U R E 1mentioning
confidence: 99%
“…In Refs. [28][29][30][31][32][33][34][35][36][37], we can find several useful antennas having the same behaviour when they are deposited directly on the skin. For example, Ref.…”
Section: F I G U R E 1mentioning
confidence: 99%
“…A study on frequency-domain breast cancer detection found that benign, and malignant breast tissues differ in dielectric properties than healthy tissues [18][19][20][21][22][23]. The study also investigated the effect of electromagnetic wave interaction on breast cancer detection using a UWB antenna system [24][25][26][27]. The study examines various breast cancer classifiers, such as decision trees, Multi-Layer Perception (MLP), Naive Bayes (NB), Sequential Minimal Optimisation (SMO), and Instance Based for K-Nearest Neighbour (IBK) were applied on Wisconsin Breast Cancer (WBC), Wisconsin Diagnosis Breast Cancer (WDBC), and Wisconsin Prognosis Breast Cancer (WPBC) datasets.…”
Section: Introductionmentioning
confidence: 99%